Emerging problems and novel skills: a qualitative analysis on the role of occupational physicians - Calicchia, Sara; Cangiano, Giovanna; Scolamiero, Giuseppina; Capanna, Silvia; Papaleo, Bruno (La Medicina del Lavoro, 2019)
Introduction: The thorough changes in the world of employment, together with regulatory changes, have made the role of occupational health physicians increasingly complex, with an extension of the prescribing component, linked to the operational aspects of the role, as well as a greater complexity in the discretionary sphere, which also requires a number of “non-technical” skills. Objectives: This work investigates how occupational physicians experience and represent their role, with special attention paid to the person-context relationship, so as to offer reflections and useful tools for supporting this role within the participatory health and safety system in the workplaces. Methods: Using a qualitative approach, the survey has been carried out through semi-structured interviews to a sample of 22 Italian occupational health physicians who were asked to talk about their professional experience with regard to the legislative reforms, critical factors in their work, their relationship with other players in the safety system, and satisfaction with Continuous Medical Training (ECM). The interviews were analyzed using content statistics analysis software. Results: Faced with the various context constraints, occupational physicians often remain confined to their healthcare role and in their relationship with the patient-worker. This causes difficulties in intervening as overall health and safety consultants for workers in a preventive context. Traditional technical expertise, delivered through ECM Training and guidelines, is not enough to make a substantial change in practising the profession, but other types of intervention are necessary to facilitate reflection about problems and one’s own actions.